Sustainability and the Bioeconomy: Synthesis of Key Themes from the 15th ICABR Conference - Smyth, S.J.; Aerni, P.; Castle, D.; Demont, M.; Falck-Zepeda, José B.; Aarlberg, R.; Phillips, Peter W.B.; Pray, C.E.; Savastano, S.; Wesseler, J.H.H.; Zilberman, D. (2011)
The International Consortium on Applied Bioeconomy Research(ICABR) held its 15th annual conference near Rome, Italy inJune 2011. The theme of the conference was sustainability, andthis topic was addressed through numerous presentations fromacademia, government, and industry. Numerous presentationsfrom developing countries highlighted the adoption benefits ofthe biotechnologies in these countries.